Putting menopause on ice: the cryomedicalization of reproductive aging - Charlotte Kroløkke; Anna Sofie Bach (New Genetics and Society, 2020)
This article examines how cryopreserved ovarian tissue is potentiated as a menopausal prevention and/or treatment cure. Based on a multi-sited ethnographic study, the article empirically foregrounds scientific accounts and interviews with Danish female cancer patients who had ovarian tissue preserved. Using situational analysis as a methodological approach along with analytical perspectives on potentiality, we identify three framings revealing how cryotechnology intervenes with women’s reproductive aging: Cryopreservation as a risk management technology, as an optimizing technology, and as a synchronization technology. The article shows how the ability to cryopreserve ovarian tissue in order to reverse menopause draws upon an understanding of menopause as not only controllable but of cryopreservation as a resource-wise technology that manages women’s aging bodies. Suggesting “cryomedicalization” as a term, the article highlights how cryopreserved ovarian tissue (re)constitutes normative temporalities, produces new understandings of cryo-restoration and raises questions related to the cryopolitics of women’s aging.